The effectiveness of forensic evidence in the investigation of volume crime scenes - Wüllenweber, Sarah; Giles, Stephanie (Elsevier, 2021)
This study investigates the effectiveness of forensic evidence in UK volume crime investigations. The main aim was to identify characteristics of forensic evidence that influence its effectiveness in converting detections into criminal charges, as well as to critically consider the effectiveness of a recent service level agreement (SLA) implemented by Wiltshire Police, which aimed at reducing CSI attendance. The sample consisted of 445 police recorded cases received from Wiltshire Police. Presence or absence and location-related characteristics of fingerprint, DNA, and footwear evidence were evaluated on the effectiveness of forensic evidence and examined within the contexts of different volume crimes. Results showed a high level of correlation in converting detections into criminal charges where the presence of DNA, footwear, and multiple evidence types was recorded; and a positive correlation between forensic evidence ineffectiveness and presence of fingerprints, particularly in residential burglaries. Differences between individual offence types were expressed. The most prominent feature influencing the effectiveness of forensic evidence was found to be related to the movability of the exhibit associated with the recovered evidence, with DNA recovered from non-movable items presenting the strongest effectiveness. Cases processed after the implementation of the SLA did not show significant differences in forensic evidence effectiveness as compared to cases processed prior to the SLA, however, they demonstrated a lack in effectiveness of DNA evidence. The findings of the current research provide a better understanding of the contextual influences on the potential of forensic evidence and can support improvement of crime scene screening and CSI resource deployment.
Keywords: Forensic evidence; Volume crimes; Fingerprints